Human Metastatic Melanoma Cell Lines Panel for In Vitro and In Vivo Investigations - Ekaterina N. Kosobokova; Nadezhda A. Kalinina; Ksenia M. Konoplina; Anastasiia A. Malchenkova; Alexandra E. Evdokimova; Marina V. Piniugina; Irina I. Khan; Ilya A. Kislyak; Anna A. Basharina; Anna N. Grishanina; Anna A. Rudakova; Pavel O. Varaksa; et al. (MDPI AG, 2024)
The melanoma origin of cell lines obtained from the axillary lymph node (mel Kas, mel Pet, and mel Lap from patients with a verified diagnosis) was confirmed by the detection of the Melan A melanocyte marker expression. A hyperdiploid (2n+) for the mel Kas line; near-diploid (2n), and in some cells near-tertaploid (4n), and even hypo-octaploid (8n) set (172-179 chromosomes) in the mel Pet cell line; and a hypotetraploid (4n−) for the mel Lap line were detected by karyotypic analysis. All three cell lines are tumorigenic; however, mel Pet demonstrates tumor growth in Balb/c nude mice only in the presence of matrigel. All three lines showed a high expression of TUBB3 and PD-L1 markers, while ERa was low (minimum for mel Pet). Significant differences in the expression level were shown for the Cyt molecular marker. In the transplantation of cells to Balb/c nude mice, a stable expression level is observed only for TUBB3. For the rest of the markers, a decrease in their expression level of varying degrees was noted when the cells were growing in solid tumors in vivo. Mutations were detected in oncogenes (BRAF, EZH2, KIT, KRAS, NRAS, ROS1) and tumor suppressor genes (CDKN2A, FAT4, KMT2C, LRP1B, PTEN, PTPRB, TP53). The detailed characterization of the cell lines makes them valuable for various scientific and regulatory experiments, particularly those involving preclinical data on antiproliferative drugs for malignant melanoma or investigations into melanoma cell properties and progression.